Fatigue shifts and scatters heart rate variability in elite endurance athletes - Schmitt, L.; Regnard, J.; Desmarets, M.; Mauny, F.; Mourot, L.; Fouillot, J.-P.; Coulmy, N.; Millet, G. (PLOS ONE, 2013)
Purpose: This longitudinal study aimed at comparing heart rate variability (HRV) in elite athletes identified either in `fatigue` or in `no-fatigue` state in `real life` conditions. Methods: 57 elite Nordic-skiers were surveyed over 4 years. R-R intervals were recorded supine (SU) and standing (ST). A fatigue state was quoted with a validated questionnaire. A multilevel linear regression model was used to analyze relationships between heart rate (HR) and HRV descriptors [total spectral power (TP), power in low (LF) and high frequency (HF) ranges expressed in ms2 and normalized units (nu)] and the status without and with fatigue. The variables not distributed normally were transformed by taking their common logarithm (log10). Results: 172 trials were identified as in a `fatigue` and 891 as in `no-fatigue` state. All supine HR and HRV parameters (Beta±SE) were significantly different (P<0.0001) between `fatigue` and `no-fatigue`: HRSU (+6.27±0.61 bpm), logTPSU (-0.36±0.04), logLFSU (-0.27±0.04), logHFSU (-0.46±0.05), logLF/HFSU (+0.19±0.03), HFSU(nu) (-9.55±1.33). Differences were also significant (P<0.0001) in standing: HRST (+8.83±0.89), logTPST (-0.28±0.03), logLFST (-0.29±0.03), logHFST (-0.32±0.04). Also, intra-individual variance of HRV parameters was larger (P<0.05) in the `fatigue` state (logTPSU: 0.26 vs. 0.07, logLFSU: 0.28 vs. 0.11, logHFSU: 0.32 vs. 0.08, logTPST: 0.13 vs. 0.07, logLFST: 0.16 vs. 0.07, logHFST: 0.25 vs. 0.14). Conclusion: HRV was significantly lower in 'fatigue' vs. 'no-fatigue' but accompanied with larger intra-individual variance of HRV parameters in 'fatigue'. The broader intra-individual variance of HRV parameters might encompass different changes from no-fatigue state, possibly reflecting different fatigue-induced alterations of HRV pattern.